2014
DOI: 10.1371/journal.pone.0113702
|View full text |Cite|
|
Sign up to set email alerts
|

Epstein-Barr Virus and Human Papillomavirus Infections and Genotype Distribution in Head and Neck Cancers

Abstract: ObjectiveTo investigate the prevalence, genotypes, and prognostic values of Epstein-Barr virus (EBV) and human papillomavirus (HPV) infections in Japanese patients with different types of head and neck cancer (HNC).Methods and MaterialsHPV and EBV DNA, EBV genotypes and LMP-1 variants, and HPV mRNA expression were detected by PCR from fresh-frozen HNC samples. HPV genotypes were determined by direct sequencing, and EBV encoded RNA (EBER) was examined by in situ hybridization.ResultsOf the 209 HNC patients, 63 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 61 publications
(75 reference statements)
6
41
0
2
Order By: Relevance
“…Compiled studies have shown that most OPSCC are mediated by HPV16 (76 to 95%), followed by HPV18 (1 to 8%) with HPV33, -35, -56, -58, and -67 found infrequently (37,44,45). In 2009, the IARC recognized HPV16 as a causal agent in OPSCC (46).…”
Section: Oropharyngeal Cancermentioning
confidence: 99%
“…Compiled studies have shown that most OPSCC are mediated by HPV16 (76 to 95%), followed by HPV18 (1 to 8%) with HPV33, -35, -56, -58, and -67 found infrequently (37,44,45). In 2009, the IARC recognized HPV16 as a causal agent in OPSCC (46).…”
Section: Oropharyngeal Cancermentioning
confidence: 99%
“…Elevated IgA antibody titers to EBV capsid and early antigens is predictive of NPC development within a window of about 3 years (Henle et al, 1970; Ji et al, 2007). Despite the nearly complete association of EBV in type 2/3 endemic NPC, HPV has been detected at frequencies ranging from 10 – 47% in endemic NPC cohorts from Japan, Iran, Morocco, and China (Deng et al, 2014; Laantri et al, 2011; Mirzamani et al, 2006; Tung et al, 1999). Although both low-risk and high-risk HPVs (6, 11, 16, and 18) were detected, HPV16 and 18 were more prevalent, accounting for 66.7% of HPV-positive NPC tumors in a Chinese cohort (Tung et al, 1999).…”
Section: Hpv and Herpesvirusesmentioning
confidence: 99%
“…A study recently performed on a cohort of Japanese HNC to investigate the frequency of EBV and HPV in fresh frozen samples to analyze the effect of co-infection on different types of HNC. The findings revealed that although HPV and EBV are highly prevalent in subset of oropharynx and nasopharynx of HNC simultaneous infection or co-infection is rare [1]. Another report published this year by Cooper et al reported that although oncolytic reovirus demonstrate significant destruction of HNC cells the oncolysis is significantly greater in HPV negative HNC cell lines as compared to HPV positive ones [9].…”
Section: Introductionmentioning
confidence: 96%
“…Many cancers including the head and neck group of cancers (HNC) are caused by oncogenic strains of viruses like Human papillomavirus (HPV) and Epstein -Barr virus (EBV) [1]. Interestingly certain viruses also possess the cancer eliminating properties and reovirus (RV) a double stranded RNA virus is a prominent one with significant research guided relevance [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation